Burnout and resilience among intensive care workers facing the end of the COVID-19 pandemic: a cross-sectional study - Ana Irene Carlos de Medeiros; Elizabeth De Francisco Daher; Xinaida Taligare Vasconcelos Lima; Antonio George de Matos Cavalcante; Marcelo Alcântara Holanda; Eanes Delgado Pereira (São Paulo Medical Journal)
ABSTRACT BACKGROUND: Burnout is a global problem, and resilience may support the well-being of healthcare workers (HCWs) in stressful conditions. OBJECTIVES: This study aimed to evaluate the association between burnout and resilience among HCWs in intensive care units (ICU) during the coronavirus disease 2019 (COVID-19) pandemic. DESIGN AND SETTING: A cross-sectional study was conducted in the ICU of four public hospitals in Fortaleza, Brazil. METHODS: A face-to-face survey was conducted among HCWs in the ICUs of four public hospitals in Fortaleza between January and August 2023. The participants completed questionnaires on burnout and resilience. RESULTS: A total of 194 professionals, including physichians (24%), nurses (29%), nursing technicians (25%), and physiotherapists (22%), completed questionnaires on burnout and resilience through face-toface interviews. Most professionals (62%) presented with overall burnout symptoms, and an inverse association was observed between resilience and burnout. However, 16 of the 44 (34%) HCWs with the highest resilience scores experienced burnout. Furthermore, younger age and higher workload were associated with a higher prevalence of burnout. CONCLUSION: Determinants of burnout were identified among ICU staff members during the last year of the COVID-19 pandemic. Resilience helped HCWs cope with burnout. However, some of the most resilient HCWs presented with high levels of burnout. Efforts are necessary to implement resilience-building tools, yet public health policies to improve ICU organizational issues are more important and urgent for promoting sustainable well-being among professionals, particularly during challenges such as pandemics. Introducing resilience-building tools and implementing public health policies are necessary to improve ICU management and promote sustainable well-being among healthcare workers in high workload settings.